Exercise and Respiratory Tract Viral Infections - Martin, Stephen A. (2009)
Prolonged, intense exercise causes immunosuppression, while moderate intensity exercise improves immune function and potentially reduces risk and severity of respiratory viral infection. Here, based upon available evidence, we present a model whereby moderate exercise-induced increases in stress hormones reduce excessive local inflammation and skew the immune response away from a Th1 and towards a Th2 phenotype, thus improving outcomes following respiratory viral infection.